Nitrate And Phosphorus Removal From Synthetic Water And Their Coupling Effect Using Nanofiltration Membrane - Aizadshah, Fatima Zahara (Universiti Sains Malaysia, 2018)
Nitrate and phosphate contamination of groundwater is a growing problem both in developed and developing countries. Such contamination comes mainly from the intensive use of fertilizers in agriculture, improper discharges of industrial effluents and effluents from intensive farming. Nanofiltration (NF) is chosen as the treatment for nitrate and phosphorus removal from contaminated waters. In this work, the removal of nitrates and phosphate from synthetic water using a commercial NF270 and NF90 membrane is studied. The efficiency of both membranes is evaluated based on the influence of transmembrane pressure, stirring speed and initial concentration of each solute on rejection and flux. NF90 shows higher rejection on nitrate (97.8%) while NF270 shows higher removal of phosphate (99.1%) which shows that NO3- removal is via diffusional control while PO43-removal is via charge repulsion control. The coupling effect of nitrate and phosphate was also investigated. It was proven that rejection of nitrate is greatly influenced by the presence of phosphate ions due to the electro-neutrality principle. Lastly, effect of stirring speed on flux and the mass transfer coefficient were also established for each membrane. NF270 shows linear increase in mass transfer coefficient against stirring speed for both individual nitrate and phosphate removal. This behavior of the NF270 membrane can be explained by relatively larger pore size of the NF270 membrane allowing more solution to pass through thus less concentration polarisation which describes the accumulation of the species being retained close to the surface of the membrane.